John Stuart Mill and the art of life - Eggleston, Ben, 1971-; Miller, Dale E., 1966-; Weinstein, D. (David), 1949- (New York ; Oxford : Oxford University Press, 2010)
The 'Art of Life' is John Stuart Mill's name for his account of practical reason. In this volume, 11 leading scholars elucidate this fundamental, but widely neglected, element of Mill's thought.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 16, 2010).
Keywords: Mill, John Stuart, -- 1806-1873.; Practical reason